(untitled) (Clinics, 2015)
OBJECTIVES:Colorectal cancer is the third leading cause of cancer death in the United States. The American College of Gastroenterology recommends screening for first-degree relatives of patients diagnosed with colorectal cancer before the age of 50. A colonoscopy is one of the most commonly recommended exams due to its specificity and the possibility to resect pre-malignant lesions. Nevertheless, the rate of physician adherence to this recommendation is unknown.METHODS:This transversal study was performed at a major cancer center in Brazil with 62 patients, aged 18 to 50, who completed a questionnaire on information received from their physicians regarding screening their first-degree relatives. We used the answers from patients who provided explicit consent.RESULTS:Two hundred and three patients were eligible to participate and 93 (45.8%) agreed to complete the questionnaire. Twenty-three questionnaires (24.73%) were returned and 39 were completed by telephone. Of the patients who answered the questionnaire, 39 (62.9%) had received a colonoscopy recommendation for their first-degree relatives and 23 (37.1%) were not informed of the recommendation. Among the patients who received the recommendations, 20.51% affirmed that all relatives completed the exam and 51.28% stated that no relatives completed the exam.DISCUSSION:The adherence rate of our physicians to the ACG guideline recommendations was 62.9%. Considering that our study was performed at a leading center for cancer treatment in Latin America, we had expected better adherence. The results show that adherence to the colorectal cancer screening recommendations for high-risk patients must be improved.